2004
DOI: 10.1182/blood.v104.11.664.664
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Glycoprotein Osteopontin Is a Stem Cell Niche Constituent That Constrains the Hematopoietic Stem Cell Pool Size.

Abstract: Stem cells reside in a physical niche where a balance of signals controls their growth, differentiation and death. Niche components have generally been defined in terms of cells and positive effects on stem cell maintenance or expansion. Here we define a role for a matrix glycoprotein that provides a constraining function in the hematopoietic stem cell niche. Osteopontin (OPN) is an abundant glycoprotein in bone that can function as either cytokine or cell adhesion mediator. It is known to be produced by multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since osteoblasts are important in this process, it was hypothesized that continuous activation of osteoblasts would affect HSC behavior. Indeed, when osteoblasts are activated by parathyroid hormone, many factors are secreted, including Sfrp4, Bmp4, Jag1, TGF and Opn (129,130). Studies of Opn-deficient mice demonstrated that in the absence of Opn, the number of HSC increases in a stromal cell-dependent manner.…”
Section: Secreted Factors That Retain Stem Cell Pool and Niche Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Since osteoblasts are important in this process, it was hypothesized that continuous activation of osteoblasts would affect HSC behavior. Indeed, when osteoblasts are activated by parathyroid hormone, many factors are secreted, including Sfrp4, Bmp4, Jag1, TGF and Opn (129,130). Studies of Opn-deficient mice demonstrated that in the absence of Opn, the number of HSC increases in a stromal cell-dependent manner.…”
Section: Secreted Factors That Retain Stem Cell Pool and Niche Sizementioning
confidence: 99%
“…This, in turn, is associated with increased stromal Jag1 and Angpt1 expression and a reduction in primitive hematopoietic cell apoptosis. Activating osteoblasts with parathyroid hormone in the absence of Opn induces a strong increase in stem cells, indicating that physiological Opn limits the affects of niche activation on HSC cycling (130).…”
Section: Secreted Factors That Retain Stem Cell Pool and Niche Sizementioning
confidence: 99%